مُقوّمات التفكير الفلسفي عند ابن حزم الظاهري - بوشافة الميلود (University of Eloued جامعة الوادي, 2024)
تسلّط هذه الورقة البحثية الضوء على أحد أهم مفكري الأندلس في القرن الخامس الهجري، ويتعلق الأمر بابن حزم المؤسس الأبرز للمنهج الظاهري. وقد حاولنا التركيز من خلالها على توجهه الفلسفي،على اعتبار أن الدراسات التي تناولت ابن حزم ركزت في مجملها على الوجه الأول للظاهرية، المتمثل في جانبها الفقهي والأصولي والشرعي وقد ترتب عن كل هذا، أن أُغفل شقها الثاني الذي يعكسه مناصرتها للعقل والمعقول، ودفاعها عن علوم الأوائل، والتي تمثل الأسس النظرية والمعرفية التي يستند إليها، الذي يبلور مشروعا ثقافيا نظريا ذا مطامح فلسفية. وقد توصلنا من خلال هذه الدراسة إلى عدة نتائج أهمها: أن ابن حزم ليس فقيها وأصوليا فقط، بل فيلسوفا ومتكلما، كما أنه استطاع تأسيس نظرية في المعرفة، وتحديد طبيعتها، كما أنه مارس النقد، من خلال نقده للمواقف الكلامية المنحرفة. This paper sheds light on one of the most important thinkers of Andalusia in the fifth century AH, and it is related to Ibn Hazm, the most prominent founder of the Al Dhaheri method. We have tried to focus through it on his philosophical orientation, given that the studies that dealt with Ibn Hazm focused in their entirety on the first aspect of the phenomenon, which is represented in its jurisprudential, fundamental and legal aspects. The first ones, which represent the theoretical and epistemological foundations on which it is based, which crystallizes a theoretical cultural project with philosophical aspirations. Through this study, we reached several conclusions, the most important of which are: that Ibn Hazm is not only a jurist and fundamentalist, but also a philosopher and orator. He was also able to establish a theory of knowledge and determine its nature. He also practiced criticism through his criticism of deviant verbal positions.
Keywords: ابن حزم الأندلسي؛ العقل؛ نظرية المعرفة؛ التأويل؛ المنطق.